2003
DOI: 10.1023/b:cyto.0000015838.06536.de
|View full text |Cite
|
Sign up to set email alerts
|

Lactate dehydrogenase enhances immunoglobulin production by human hybridoma and human peripheral blood lymphocytes

Abstract: Lactate dehydrogenase (LDH) derived from rabbit muscle enhanced IgM production by human-human hybridoma HB4C5 cells 12.4-fold at 320 g/ml under serum-free conditions. LDHs from pig muscle and pig heart also accelerated IgM production 8.4-and 6.4-fold, respectively. The immunoglobulin production stimulating activity of LDH was not accompanied by activation of cell proliferation. LDH from rabbit muscle facilitated IgM and IgG production by human peripheral blood lymphocytes. This means LDH stimulates immunoglobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…It is therefore suggested that the kale extract affected the HB4C5 cells in the post-transcriptional stages such as the translational and/or protein-secreting processes to enhance the IgM production. These results are consistent with other IPSFs; [16][17][18][19] for example, lysozyme is one of the strong IPSFs and accelerated IgM production in both Act D-treated and non-treated HB4C5 cells. 20) The stimulatory effect of the kale extract on the Act Dtreated HB4C5 cells was lower than that on the intact HB4C5 cells.…”
Section: Effect Of the Kale Extract At The Transcriptional Levelsupporting
confidence: 88%
“…It is therefore suggested that the kale extract affected the HB4C5 cells in the post-transcriptional stages such as the translational and/or protein-secreting processes to enhance the IgM production. These results are consistent with other IPSFs; [16][17][18][19] for example, lysozyme is one of the strong IPSFs and accelerated IgM production in both Act D-treated and non-treated HB4C5 cells. 20) The stimulatory effect of the kale extract on the Act Dtreated HB4C5 cells was lower than that on the intact HB4C5 cells.…”
Section: Effect Of the Kale Extract At The Transcriptional Levelsupporting
confidence: 88%
“…Over the past decade, various approaches such as genetic engineering, clone selection, medium optimization, and reactor engineering have dramatically improved production (Takenouchi and Sugahara 2003). The addition of an enhancer has also proven effective.…”
Section: Introductionmentioning
confidence: 99%
“…It was also confirmed that the immunomodulatory activity of LDH does not depend on its enzyme activity (Sugahara et al 1998). Thus, it was thinkable that the protein structure of LDH stimulates lymphocytes (Takenouchi and Sugahara 2002). LDH ubiquitously and abundantly exists in most of the tissues in humans, especially in kidney, heart, skeletal muscle, pancreas, spleen, liver, and lung.…”
Section: Discussionmentioning
confidence: 99%
“…LDH is known to play a crucial role in maintaining aerobic metabolism by converting lactate to pyruvate in muscle and to exist ubiquitously not only in fish but also in all vertebrate organisms. We previously evaluated that the immunostimulatory effect of LDH is a novel function, which is independent of the enzymatic activity of the enzyme (Sugahara et al 1998;Takenouchi and Sugahara 2002). In addition, oral administration of LDH increased the IgA level in serum from BALB/c mice (Daifuku et al 2012b).…”
Section: Introductionmentioning
confidence: 99%